Low-Level Motion Characteristics Do Not Account for Perceptions of Stream-Bounce Stimuli. (January 2017) - Zeljko, Mick; Grove, Philip M.
The stream-bounce effect refers to a bistable motion stimulus that is interpreted as two targets either "streaming" past or "bouncing" off one another, and the manipulations that bias responses. Directional bias, according to Bertenthal et al., is an account of the effect proposing that low-level motion integration promotes streaming, and its disruption leads to bouncing, and it is sometimes cited either directly in a bottom-up fashion or indirectly under top-down control despite Sekuler and Sekuler finding evidence inconsistent with it. We tested two key aspects of the hypothesis: (a) comparable changes in speed should produce comparable disruptions and lead to similar effects; and (b) speed changes alone should disrupt integration without the need for additional more complex changes of motion. We found that target motion influences stream-bounce perception, but not as directional bias predicts. Our results support Sekuler and Sekuler and argue against the low-level motion signals driving perceptual outcomes in stream-bounce displays (directly or indirectly) and point to higher level inferential processes involving perceptual history and expectation. Directional bias as a mechanism should be abandoned and either another specific bottom-up process must be proposed and tested or consideration should be given to top-down factors alone driving the effect.